2010
DOI: 10.1007/s00198-010-1210-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations of fat mass and fat distribution with bone mineral density in pre- and postmenopausal Chinese women

Abstract: There were different associations of FM and fat distribution with BMD in pre- and postmenopausal Chinese women. Increased central body fat had a negative association with BMD. Our findings may have significant implications in the prevention of menopause-related osteoporosis through reducing centralized fat deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
63
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 48 publications
3
63
2
2
Order By: Relevance
“…First, in contrast to prior assumptions that fat mass begets bone mass, it is now clear from epidemiological studies that obesity tracks with osteoporosis (18)(19)(20). Notably, there is a negative correlation between bone mass and fat mass in both rodents and in people [e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, in contrast to prior assumptions that fat mass begets bone mass, it is now clear from epidemiological studies that obesity tracks with osteoporosis (18)(19)(20). Notably, there is a negative correlation between bone mass and fat mass in both rodents and in people [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, there is a negative correlation between bone mass and fat mass in both rodents and in people [e.g. (18,20)]. Second, during the menopausal transition, the rapid bone loss that leads to high fracture rates accompanies the onset of visceral fat accumulation (2, 3, 6); the latter, if left unchecked, predisposes to metabolic syndrome, cardiovascular disease, and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This led to a number of studies examining the relationship between childhood obesity and bone with conflicting results, with some suggesting a positive relationship between adiposity and bone with others suggesting that excess fat is detrimental to the developing skeleton [2]. The issue of 'obesity' and the effect on the developing and adult skeleton was perhaps considered overly simplistic and subsequent work focusing on fat distribution demonstrated that, as with other metabolic conditions, it is visceral fat that appears to have a deleterious effect on the skeleton [4,5] although again not all studies in adults are in agreement with this [3]. The advent of high resolution pQCT (HRpQCT) has allowed us to examine the in-vivo relationship between fat and bone at a microstructural level in children with results demonstrating that the trabecular architecture understanding of how adipokines affect and control energy regulation resulted in a shift from initial in vitro findings attempting to elucidate the direct and systemic effects of adipokines on skeletal cells, to determine how key areas of the brain such as the hypothalamus may control the skeleton.…”
mentioning
confidence: 99%
“…These diseases have remained the leading causes of death globally [5]. Osteoporosis is defined as a loss of basic metals from bones which increases susceptibility to bone fractures involving the lumbar spine, femoral neck and wrist [6] [7]. This research aimed to determine the relationship between obesity and bone density in Saudi women.…”
Section: Introductionmentioning
confidence: 99%